O sítio em Sambizanga: mitos e tradições entre Monteiro Lobato e Luandino Vieira - Galhego, Vilma Aparecida (2009)
This research aims to study comparatively O Minotauro of Monteiro Lobato, for the public children s; and the short story Estória da galinha e do ovo, in this book Luuanda, of Luandino Vieira, that has the adult as public reader. The main objective is to learn how each author produces aesthetically myth and the rescue of tradition in the scene space of childhood. Each author, Lobato and Luandino, although belonging to different cultures, make such space, particularly, creating, therefore, two differents issues to be treated: the first one refers to the inscription of children in these works, once are intended for different readers; the second one questions the interaction of these readers with the space in different destination: sometimes for the adult, sometimes for the child. The theoretical foundation is based on the methodology of Comparative Literature, in works of Tânia Franco Carvalhal. In regarding to the study of orality, we refer to the recovery of tradition, from the works of Paul Zumthor; Jean Pierre Vernant gives us support to the study of myth. The research is divided into three chapters: the first chapter deals with a short introduction about the investigative function of Comparative Literature and presents the concept of childhood in the Brazilian and Angolan literatures, next, show the space of Luanda and the "Sítio do pica-pau amarelo" as sceneries of representation. The second one deals with the construction of the infant child itself in the two respective narratives. The third one collects the way each author works the myth and, through the orality, get the tradition back. We, after all, find that the way the child interacts with the fictional space is in dependence of a storyteller, in the place and in the scenes ordered by the poetic of the space through the playful action - convergence point of communication for both receptors, the adult and the child, without others borders